8 - Du sens d’une lecture ontologico-théologique de la mondialisation saisie comme destin tragique de l’humanité - Kouassi, Léonard Kouadio (Africa Development, 2021)
By operating an archeology of the meaning of the idea of destiny through the adventure of mankind on earth, we are turning up where thought was done daily for the first time among the ancients. This is of course the vision of the world as conceived by the Presocratics. This world, according to them, would obey to the law of Necessity. It’s this law, which tragically, structures, the course of the world. Such idea has been confirmed by some greatest thinkers and religious figures in world history. It is precisely for this reason that the idea of an apocalyptic globalization reinforces the tragic sense of fate. This is the main idea that tries to convey this article.